Effect of environmental factors on the corrosion behavior of CoCrNi and CoCrFeMnNi alloys in 3.5 wt% NaCl solution - Ruizhen Xie; Yifan Wei; Kunjie Luo; Naiming Lin; Yuan Yu; Peng Cheng; Qunfeng Zeng (Journal of Materials Research and Technology)
This study investigates the influence of environmental factors on the corrosion behavior of CoCrNi medium-entropy alloy (MEA) and CoCrFeMnNi high-entropy alloy (HEA) in a 3.5 wt% NaCl solution. The evaluation was conducted through electrochemical testing, immersion experiment, scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS) analysis. Polarization curves indicate that both alloys undergo passivation, with CoCrNi exhibiting superior corrosion resistance due to the lower electrochemical activity. In a dynamic environment, the CoCrNi exhibits a lower self-corrosion current density, further confirming its corrosion resistance. Impedance spectroscopy analysis reveals a more robust passivation film on the surface of CoCrNi. Immersion experiments show that the weight change of CoCrNi remains relatively stable in both static and dynamic environments, while the weight change of CoCrFeMnNi varies significantly. Therefore, when selecting corrosion-resistant materials, it is essential to consider the specific operating environment and requirements.